(untitled) (Communication & Society, 2018)
This paper examines some innovative practices of citizen engagement strategy implemented by Tokyo 2020 in the pre-game period. Hosting a sports megaevent such as the Olympic Games is a key milestone in urban history and reputation of any city. The challenge of celebrating an outstanding global event with a long-lasting positive impact on the place requires the commitment and engagement of all urban stakeholders as the hosting city needs to maximize the number of supporters who share the games’ vision and embrace the Olympic experience. The role of citizens as creators and prescribers of urban reality is increasingly recognized in the field of place branding as it confronts the traditional top-down agenda-setting approach with a new collaborative paradigm and participatory culture. The city of Tokyo has initiated the implementation of its comprehensive strategy for hosting its second Olympic Games in 2020. The foundation plan of the 2020 Games identifies the engagement strategy as one of the key strategic pillars of the event aimed at ensuring an inclusive and active participatory nature of the Games celebration. The research is guided by an exploratory case study approach to assess the citizen engagement strategy and participatory frameworks within the context of the Olympic mega-event to be held in Tokyo in 2020. The examination of some innovative initiatives in the pre-game period such as the national call for the creation of Olympic medals, the Olympic mascots selection process and the Volunteering program, reveals a series meaningful drivers of citizen engagement strategy of Tokyo 2020 Olympic Games ranging from the access to a specific Olympic knowledge and sports experience to a personal self-realization and community empowerment, among others. The research aims at contributing to further academic discussion and effective practice of citizens´ engagement in place making through sports mega-events in such a way as to ensure a truly inclusive, inspiring and meaningful nature of these global happenings.